Computationally designed haemagglutinin with nanocage plug-and-display elicits pan-H5 influenza vaccine responses - Chloe Qingzhou Huang; Rory A. Hills; George W. Carnell; Sneha Vishwanath; Ernest T. Aguinam; Andrew C.Y. Chan; Phil Palmer; Laura O’Reilly; Paul Tonks; Nigel Temperton; Simon D.W. Frost; Laurence S. Tiley; et al. (Emerging Microbes and Infections, 2025)
The increasing spread of highly pathogenic avian influenza (HPAI) A/H5 viruses poses a pandemic threat. Circulating clade 2.3.4.4b viruses have demonstrated rapid transcontinental dissemination, extensive reassortment, epizootic spread and potential sustained mammal-to-mammal transmission, signifying a heightened risk of becoming a human pathogen of high consequence. A broadly protective, future-proof vaccine against multiple clades of H5 influenza is urgently needed for pandemic preparedness. Here, we combine two novel vaccine technologies to generate a Digitally Immune Optimised and Selected H5 antigen (DIOSvax-H5inter) displayed multivalently on the mi3 nanocage using the SpyTag003/SpyCatcher003 conjugation system. Mice immunized with DIOSvax-H5inter Homotypic Nanocages at low doses demonstrate potent, cross-clade neutralizing antibody and T cell responses against diverse H5 strains. DIOSvax-H5inter Homotypic Nanocages provide a scalable vaccine candidate with the potential for pan-H5 protection against drifted or newly emergent H5 strains. This World Health Organization preferred characteristic is essential for prospective strategic stockpiling in the pre-pandemic phase.